Techno-economic evaluation of biomass-to-fuels with solid-oxide electrolyzer. (15th July 2020) - Zhang, Hanfei; Wang, Ligang; Van herle, Jan; Maréchal, François; Desideri, Umberto
Highlights: Biomass-to-fuels with solid-oxide electrolyzer investigated techno-economically. Biomass-to-fuels with steam electrolysis achieve high efficiencies of 56-68%. Biomass-to-fuels with co-electrolysis show economic advantages. Biomass-to-fuels with co-electrolysis enable continuous, highly-flexible operation. Abstract: Thermochemical biomass-to-fuel conversion requires an increased hydrogen concentration in the syngas derived from gasification, which is currently achieved by water–gas-shift reaction and CO2 removal. State-of-the-art biomass-to-fuels convert less than half of the biomass carbon with the remaining emitted as CO2 . Full conversion of biomass carbon can be achieved by integrating solid-oxide electrolyzer with different concepts: (1) steam electrolysis with the hydrogen produced injected into syngas, and (2) co-electrolysis of CO2 and H2 O to convert the CO2 captured from the syngas. This paper investigates techno-economically steam- or co-electrolysis-based biomass-to-fuel processes for producing synthetic natural gas, methanol, dimethyl ether and jet fuel, considering system-level heat integration and optimal placement of steam cycles for heat recovery. The results show that state-of-the-art biomass-to-fuels achieve similar energy efficiencies of 48–51% (based on a lower heating value) for the four different fuels. The integrated concept with steam electrolysis achieves the highest energy efficiency: 68% for synthetic natural gas, 64% for methanol, 63% for dimethyl ether, and 56% for jet fuel. The integrated concept with co-electrolysis can enhance the state-of-the-art energy efficiency to 66% for synthetic natural gas, 61% for methanol, and 54% for jet fuel. The biomass-to-dimethyl ether with co-electrolysis only reaches an efficiency of 49%, due to additional heat demand. The levelized cost of the product of the integrated concepts highly depends on the price and availability of renewable electricity. The concept with co-electrolysis allows for additional operation flexibility without renewable electricity, resulting in high annual production. Thus, with limited annual available hours of renewable electricity, biomass-to-fuel with co-electrolysis is more economically convenient than that with steam electrolysis. For a plant scale of 60 MWth biomass input with the renewable electricity available for 1800 h annually, the levelized cost of product of biomass-to-synthesis-natural-gas with co-electrolysis is 35 $/GJ, 20% lower than that with steam-electrolysis.